35. A CASE REPORT: METATARSAL TRANSFER FOR GIANT CELL TUMOR OF METACARPAL (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe medical history, surgical method of metatarsal transfer for metacarpal giant cell tumor (GCT) and to report treatment result of it after 13-year follow-up. Methods: A single case study design, the patient with GCT involving 5th metacarpal bone of right hand, who was GCT resected and reconstructed with free osteoarticular metatarsal allograft then followed up for 13 years at Orthopedic Oncology and Musculoskeletal Disease Department, Ho Chi Minh City Hospital of Trauma and Orthopedics from December 2010 to December 2023. Results: The study’s participant is a 36-year-old male patient with a tumor size 1x1.5x2 cm, relatively hard density, quite clear limit, motionless, mild pain when press. The range of motion of metacarpophalangeal joint in 5th finger of the right hand is 10-90 degrees. Movement of other joints is within normal limit. Grip strength of the right hand with GCT is 10 kgf. Treatment method is resection of metacarpal GCT and reconstruction by non-vascularised 4th metatarsal. In the foot region, metatarsal is reconstructed by illiac crest bone. Capsule and ligaments of the transferred metatarsal were sutured to the corresponding capsule and ligaments at the recipient site. Forearm splint and iselin splint for the 5th finger of right hand, cast splint on the left foot. Physical therapy after surgery. Seven days after surgery, remove splint and practise moving fingers, wrist, ankle then put on the splints after exercise. Removed cast splint after 6 weeks and forearm splint after 4 months. 1 year after surgery, removed kirschner and the patient resumed work. At 13 year follow up, recurrence has not been detected, transferred metatarsal harvested well. The range of motion of metacarpophalangeal joint in 5th finger of the right hand is 10-70 degrees. Function of the hand is good. Grip strength of the hand is 30 kgf. Conclusion: Our treatment and surgical method of metacarpol GCT presented good result. Range of motion, function and strength grip of the patient’s hand was nearly normal.
Keywords: Giant cell tumor, giant cell tumor of bone, bone allograft.